THE STUDENTS’ PERCEPTIONS ON THE USE OF INSTRUCTIONAL MEDIA BY THE ENGLISH TEACHERS OF SMPN 25 PEKANBARU - Emi Nurmawati; Supriusman Supriusman; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aimed at finding the students’ perceptions on the use of instructional media by the English teachers. 30 students were taken as the sample of this research Using cluster random sampling. This research employed quantitative method of data collection. The data were collected from a questionnaire. The questionnaire consists of 15 items. The findings of this study revealed that there were some level categories of instructional media used by the English teachers, from very high level to the fair level. Based on the results of the research: firstly, using Boards showed that this instructional media was used at very high level with its percentage of 93.3%. Secondly, using Course Book showed that it was at high level with the percentage of 75.1%. Next, using Real Object was at fair level with percentage 60.7%. Then, using Computer-based Presentation Technology was at fair level with percentage of 53.1%. Fifth, LCD Projector was also at fair level with percentage of 48.7%. Finally, using Pictures was also at fair level with percentage of 46%. It can be said that the English teachers always used instructional media (using white board) in their teaching English, and the English teachers rarely used instructional media such as (using drawings, photographs, charts) in teaching English. Nowadays in digital era, teachers need to use more interesting technological media and not only conventional media when teaching English but also use technology to ease teaching English in the school.Keywords: Perception, Instructional media, Teaching English